Transformasi Pemikiran Ekonomi Islam Ibnu Taimiyah dalam Menanggapi Isu-isu Ekonomi Kontemporer - Hamid, Abd; Thohir, Ropiqi (At-Tasharruf "Jurnal Kajian Ekonomi dan Bisnis Syariah", 2025)
The transformation of Ibn Taimiyah's Islamic economic thought has made a significant contribution to answering contemporary economic challenges. Although Ibn Taimiyah lived in the 13th and 14th centuries, his thoughts on economic justice, wealth distribution, and the role of the state in regulating the economy are still relevant to analyzing modern economic issues. Ibn Taimiyah emphasized the importance of a balance between market freedom and state involvement to create social justice and people's welfare. In the context of contemporary economics, his ideas on the prohibition of usury, price regulation, protection of consumer rights, and distribution of natural resources are the basis for solutions to overcome social inequality and the global economic crisis. This paper examines the relevance of Ibn Taimiyah's economic thought in dealing with issues such as economic inequality, unemployment, and exploitation of natural resources that are often found in the modern capitalist economic system. With an interdisciplinary approach that combines Sharia principles with economic analysis, this study shows that Ibn Taimiyah's thoughts can be an alternative to developing a more just and sustainable economic model in this era of globalization.